Report from the Field: SOME RANDOM THOUGHTS ON THE ETHICAL BEHAVIOUR Of TEACHER CANDIDATES - Bradley, Jon G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1998)
ABSTRACT. Accepting the reality thar teaching is not a fully fledged profession like other such societal occupations, student teachers find themselves being orientated into a vocation that is still attempting to carve out its rightful place in an evolving society. Until such time as teacher educators adopt a public and accountable ethical regime for teacher candidates, this quasi profession of teaching will continue to wallow in uncertainty and misdirection. RÉSUMÉ. Résignés à la réalité que l’enseignement n’est pas une profession à part entière comme d’autres professions sociales, les professeurs stagiaires se voient invités à embrasser une vocation qui tente encore de prendre la place qui lui revient dans notre société en évolution. Tant et aussi longtemps que les responsables de la formation des maîtres n’adopteront pas un régime éthique public et responsable pour les futurs enseignants, cette quasi profession continuera de croupir dans son indécision et sa mauvaise orientation.